Asymmetrical late onset motor neuropathy associated with a novel mutation in the small heat shock protein HSPB1 (HSP27). Issue 4 (14th March 2008) - James, P A; Rankin, J; Talbot, K
Abstract : Distal hereditary motor neuropathy, also known as distal spinal muscular atrophy, is characterised by slowly progressive weakness and wasting of the hands and feet and has a heterogeneous genetic basis. One form of distal hereditary motor neuropathy is associated with mutations in the gene for the small heat shock protein HSPB1 (hsp27). Families have been described in which slowly progressive, symmetrical, lower limb predominant motor weakness is usually evident by middle age. Here we report a novel mutation, G84R, in an elderly patient presenting with strikingly asymmetrical weakness. Expression of this and other known mutations in cell culture demonstrated enhanced aggregation of mutant HSPB1 protein compared with wild-type.